ChemInform Abstract: Nanowire Chemical/Biological Sensors: Status and a Roadmap for the Future - Fennell, John F. Jr; Liu, Sophie F.; Azzarelli, Joseph M.; Weis, Jonathan G.; Rochat, Sebastien; Mirica, Katherine A.; Ravnsbaek, Jens B.; Swager, Timothy M. (ChemInform, 2016)
Review: 251 refs.